Weight Loss Maintenance and Cellular Aging in the Supporting Health Through Nutrition and Exercise Study. Issue 7 (September 2018) - Mason, Ashley E.; Hecht, Frederick M.; Daubenmier, Jennifer J.; Sbarra, David A.; Lin, Jue; Moran, Patricia J.; Schleicher, Samantha G.; Acree, Michael; Prather, Aric A.; Epel, Elissa S.
ABSTRACT: Objective: The aim of the study was to determine, within a weight loss clinical trial for obesity, the impact of intervention arm, weight change, and weight loss maintenance on telomere length (TL). Methods: Adults ( N = 194) with a body mass index between 30 and 45 were randomized to a 5.5-month weight loss program with ( n = 100) or without ( n = 94) mindfulness training and identical diet-exercise guidelines. We assessed TL at baseline and 3-, 6-, and 12-month postbaseline in immune cell populations (primarily in peripheral blood mononuclear cells [PBMCs], but also in granulocytes and T and B lymphocytes). We defined weight loss maintenance as having lost at least 5% or 10% of body weight (tested in separate models) from preintervention to postintervention, and having maintained this loss at 12 months. We predicted that greater weight loss and weight loss maintenance would be associated with TL lengthening. Results: Neither weight loss intervention significantly predicted TL change nor did amount of weight change, at any time point. Across all participants, weight loss maintenance of at least 10% was associated with longer PBMC TL ( b = 239.08, 95% CI = 0.92 to 477.25, p = .049), CD8+ TL ( b = 417.26, 95% CI = 58.95 to 775.57, p = .023), and longer granulocyte TL ( b = 191.56, 95% CI = −4.23 to 387.35, p = .055) at 12 months after accounting for baseline TL. Weight loss maintenance of 5% or more was associated with longer PBMC TL ( b = 163.32, 95% CI = 4.00 to 320.62, p = .045) at 12 months after accounting for baseline TL. These tests should be interpreted in light of corrections for multiple tests. Conclusions: Among individuals with obesity, losing and maintaining a weight loss of 10% or more may lead to TL lengthening, which may portend improved immune and metabolic function. TL lengthening in this study is of unknown duration beyond 12 months and requires further study. Trial Registration :Clinicaltrials.gov identifier NCT00960414 ; Open Science Framework (OSF) preregistration:https://osf.io/t3r2g/ . Abstract : Supplemental digital content is available in the text.